(untitled) (Biological Sciences - PJSIR, 2022)
Dimethoate in treated pumpkin is separated by thin layer chromatography using silica coated chromatoplate from coextracted materials. Spot area measurement and comparison of colour are used to give a semiquantitative determina- tion of the amount of pesticide which persisted on the crop. The method is sensitive to detect upto O.I11g of dimethoate. The need for a preliminary cleanup procedure is eliminated. Residues of dimethoate in crop declined after 14 days.